2013
DOI: 10.1186/1746-6148-9-244
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metritis on luteal function in dairy cows

Abstract: Background: Disturbed uterine involution impairs ovarian function in the first weeks after calving. This study analyzed the long-term effect of metritis on luteal function of 47 lactating Holstein-Friesian cows during the first four postpartum estrous cycles. Cows with abnormal uterine enlargement and malodorous lochia were classified as having metritis (group M, n = 18), and all others were considered healthy (group H, n = 29). Luteal size was measured once between days 9 and 13 of the first (group H, n = 11;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
3
11
0
2
Order By: Relevance
“…Dietary energy restriction may decrease IGF-I concentrations, causing altered follicular growth and development of a subfunctional CL (Burns et al 1997). In addition, metritis was able to impair luteal activity transiently, but did not seem to have a long-term effect on luteal function (Struve et al 2013). Moreover, the luteal phase and the length of the interovulatory interval were both shorter in heifers with two waves of follicular development compared to those with three (Ginther et al 1989).…”
Section: Discussionmentioning
confidence: 88%
“…Dietary energy restriction may decrease IGF-I concentrations, causing altered follicular growth and development of a subfunctional CL (Burns et al 1997). In addition, metritis was able to impair luteal activity transiently, but did not seem to have a long-term effect on luteal function (Struve et al 2013). Moreover, the luteal phase and the length of the interovulatory interval were both shorter in heifers with two waves of follicular development compared to those with three (Ginther et al 1989).…”
Section: Discussionmentioning
confidence: 88%
“…Metritis cows are 11 times more at risk of prolonged luteal cycles during the postpartum period [8]. One study reported that cows with metritis showed a higher prevalence of persistent corpus luteum (CL) during the first postpartum luteal phase compared to healthy cows [10]. Moreover, cows with clinical endometritis are more likely to show anovulatory anestrus after calving or prolonged luteal phases compared to normal animals [1,8].…”
Section: Introductionmentioning
confidence: 99%
“…(). It was also reported that cows with severe bacterial metritis had smaller CL and lower levels of circulatory P 4 (Struve et al., ; Williams et al., ). In the present study, lower luteal P 4 (μg/g of CL) in the buffaloes with cytological and purulent endometritis might be due to the adverse effect of infection on the development of pre‐ovulatory follicle or growth of CL (Sheldon, Cronin, Goeetze, Donofrio, & Schuberth, ; Williams et al., ).…”
Section: Discussionmentioning
confidence: 92%